THE CYTOTOXIC EFFECT OF METHOXYACETIC ACID ON M11 CELL LINE OF THE SWISS WEBSTER MICE EMBRYO - (NIM 20605024), MADIHAH
Dimethoxyethyl phthalate (DMEP) is one of the phthalate acid ester (PAEs) that is widely used as plasticizers. DMEP and its metabolites (2-ME and MAA) were known to have toxic effects to several cell types in mammals. The purpose of this research is to detect the cytotoxicity effect of methoxyacetic acid (MAA) in M11 cell line from Swiss Webster mice embryo day 11 of gestation. The M11 cell line was generated from skeletal muscle mice embryo, which was cultivated until the fifth passages. MTT-based cytotoxicity assay was used to determine the concentration and the exposure time that was significantly reduced the number of viable cell in compare to control. This result showed that the P8 (5 mM MAA for 5 hours), P10 (10 mM MAA for 2 hours), P11 (10 mM MAA for 4 hours) and P12 (10 mM MAA for 8 hours) was significantly reduced the number of viable cell (p<0,05) in M11 cell line. These treated groups were used for chromosomal analysis and cell death observation. Chromosomal analysis was used to determine the mitotic index that was used to analyze the effect of MAA on cell proliferation. Hoechst 33258 staining and DNA fragmentation was used to determine the apoptotic cell death. Chromosomal analysis result showed that MAA decreased the mitotic index, which was means that MAA reduced the cell proliferation activity. It is assumed that the MAA ability to reduce the cell proliferation activity was related to the ability of MAA to interfere the availability of purine and pyrimidine bases, which are expected to affect DNA/RNA synthesis. The result from morphological observation with Hoechst 33258 and DNA fragmentation showed that the apoptotic cell was not significantly different between the control and treatment groups. It is suggested that MAA could reduced the number of viable cells by anoikis mechanism. MAA treatment disturbed cell adhesion and caused cell detachment from the substrate that leads to anoikis. This suggestion was based on another research that showed the effect of other acid phthalic ester (diethylhexyl phthalate - DEHP, dibuthyl phthalate - DBP) on the adhesion molecules and cytoskeletons that involved in cell adhesion. It is concluded that 5 mM MAA exposed for 8 hours or 10 mM MAA exposed for 2, 4 or 8 hours reduced the number of viable cell, but the cytotoxicity mechanism has not been determined yet. It is assumed that the mechanism was associated with the inhibition of cell proliferation and/or increase of cell death caused by disturbance in cell adhesion.